A Patient with Granulomatosus with Polyangiitis (Wegener’s Granulomatosis): ACase Report - Harris Hardian (Indonesian Rheumatology Associantion, 2023)
Background: Granulomatosus with Polyangiitis (GPA) is an Antineutrophilic Cytoplasmic Antibodies (ANCA) Associated Vasculitis (AAV)which involves small to moderate-sized vessels. GPA has a variety of clinicalmanifestations caused by tissue ischemia and organ affected. Diagnosis ofGPA remains challenging, and its actual incidence may be higher thanreported. In 1990, the American College of Rheumatology (ACR) publisheddiagnostic criteria for GPA. Guidelines of management of GPA has improvedsurvival in last decade, but results remain unsatisfactory. Induction agentswith immunosuppressive agents and glucocorticoid, and the newer agentRituximab are recommended as first choice treatment. Case presentation:A 64-year-old male presented with current episode of joint pain and a historyof recurrent respiratory tract infections. After a series of laboratory andradiologic examinations, lung biopsy was performed, and the result wassuggestive of GPA. The patient was managed with induction remission agentand reported improvement in both clinical and laboratory parameters.Conclusion: Granulomatosus with Polyangiitis is a limitedly reported case.This report was presented to raise awareness of the diagnosis when facedwith similar clinical symptoms. Early detection and diagnosis in GPA allowfor prompt and better management with the target to achieve and maintainremission, as demonstrated in this case.